English English - Rofi Chandra; Syahril Syahril; Ambiyar Ambiyar; Refdinal Refdinal (Postgraduate, University of Mataram, 2023)
The development video tutorials was carried out to address the challenges in learning CNC/CAM at Vocational High Schools (SMK), especially in the CNC/CAM subject. In this research, the 4D model (Define, Design, Develop, and Disseminate) stages of development were employed, which include needs analysis, design, development, and dissemination. The validation results by media experts and subject matter experts indicate that these video tutorials are highly suitable, with a validity percentage of 89.24% by media experts and 85% by subject matter experts. These results demonstrate that the CAM learning videos developed through the 4D model are suitable for use in the learning process. The development of video tutorials for CNC/CAM learning in vocational high schools can be an effective solution to overcome challenges in students' understanding and skills in this subject. By using the 4D model for development, the high validation results from media and subject matter experts indicate that these video tutorials have excellent quality. The use of these video tutorials is expected to enhance students' understanding and skills in the field of CNC/CAM, which are crucial for their preparation in the industrial world. Furthermore, this research also provides recommendations for utilizing these video tutorials in broader learning contexts, teacher training, and the development of other materials.